New Types of Plastering Mortars Based on Marble Powder Slime. (2016) - Molnar, Luminita Monica; Manea, Daniela Lucia
Abstract: The use of marble powder residue slimes that can be found in enormous amounts of about 100 tons/day (in the nearby of marble processing companies) to produce building materials represents an efficient manner of diminishing the resource consumption and of significantly reducing its negative impact upon the environment. Consequent to the drying of this product, a fine powder with various grain sizes can be obtained; the grains can be used as a partial or total of mortar aggregates. The experimental program in the present paper includes the production and proposal of more types of plaster mortars where the marble powder slime replaces the aggregate in a percentage of 25%, 50%, 75% and respectively 100% as well as a 15% replacement of the binder. Results show that 25% substitution of aggregate by marble powder provided the highest value of compression strength at 28 days and also the highest value to adhesion to the support layer. Also, plastering mortars with 15% substitution of cement by marble powder, at the age of 28 days, has a resistance to compression of 13 N/mm 2, approximately twice larger than that of the conventional plaster mortar. The present paper is dedicated to the study of the physical and mechanical properties of the plaster mortars in both fresh state and hardened state in their development in time.